Proton channel Hv1 modulates microglial responses to neurological disorders - Stratmann, Maite; Gagliardi, Caterina; Capasso, Melania (Frontiers in Biophysics, 2025)
Proton channels are transmembrane proteins that enable selective proton (H+) transport. The voltage-gated proton channel Hv1 or HVCN1 is the only one found in mammalian cells, primarily in immune cells, where it facilitates rapid proton extrusion in response to membrane depolarization, mediating outward proton currents. Therefore, it is well equipped to support NADPH-oxidase function, facilitating the proton flux that maintains physiological pH and membrane potential for efficient reactive oxygen species (ROS) production. In the central nervous system (CNS), Hv1 is predominantly found in microglia. Its role in microglia homeostasis is yet to be elucidated; however, recent research has highlighted its involvement in neurological conditions, including demyelinating disease, spinal cord injury, stroke, and Parkinsonism. These studies have shown beneficial effects of Hv1 deletion, including improved neurological function, reduced microglial activation, enhanced myelination, and decreased neuroinflammation. This review explores the role of Hv1 in the CNS and its potential as a therapeutic target in neurodegenerative diseases.